Prove LHS = RHS
(a+b)³ = a³+b³+3a²b+3ab²
Answers
Answered by
8
Hi 0 ↓ ,
LHS = (a+b)³
(a+b)³ = (a+b) (a+b) (a+b)
= (a+b)² (a+b)
(a+b)² = a² + b² + 2ab
so ,
(a+b)³ = (a² + b² + 2ab) (a+b)
multiply the binomials ,
we get ,
= a³ + 2a²b + ab² +a²b + 2ab² +b³
RHS = a³+ b³ + 3a²b + 3ab²
∴ LHS = RHS
LHS = (a+b)³
(a+b)³ = (a+b) (a+b) (a+b)
= (a+b)² (a+b)
(a+b)² = a² + b² + 2ab
so ,
(a+b)³ = (a² + b² + 2ab) (a+b)
multiply the binomials ,
we get ,
= a³ + 2a²b + ab² +a²b + 2ab² +b³
RHS = a³+ b³ + 3a²b + 3ab²
∴ LHS = RHS
Maheshmmmm:
a longer method according to class 8
Answered by
3
(a+b)³ = (a+b)(a+b)(a+b)
= [(a+b)(a+b)](a+b)
= [a(a+b)+b(a+b)](a+b)
= [a²+ab+ab+b²](a+b)
= [a²+2ab+b²](a+b)
= a(a²+2ab+b²)+b(a²+2ab+b²)
= a³+2a²b+ab²+a²b+2ab²+b³
= a³+b³+3a²b+3ab²
Hence proved
= [(a+b)(a+b)](a+b)
= [a(a+b)+b(a+b)](a+b)
= [a²+ab+ab+b²](a+b)
= [a²+2ab+b²](a+b)
= a(a²+2ab+b²)+b(a²+2ab+b²)
= a³+2a²b+ab²+a²b+2ab²+b³
= a³+b³+3a²b+3ab²
Hence proved
Similar questions